Indigenous-Municipal Legal Relationships: Moving Beyond the Duty to Consult and Accommodate - Flynn, Alexandra (Allard Research Commons, 2021)
This paper examines the path forward for Indigenous-municipal relationships in regard to the land use planning process. While the arguments in the paper apply broadly, I focus on the unique legalities of planning approaches in Ontario. The aim is to argue that municipal planning – using the example of the Ontario planning model more specifically – should not frame its responsibilities with First Nations and Indigenous peoples based on the requirements of the duty to consult, which is a problematic singular framework in grounding a nation-to-nation relationship. The duty to consult as the basis of Indigenous-settler relationships has not led to sufficient recognition of the role of Indigenous communities in the planning context. While the duty to consult and accommodate has indeed been used to ground some decisions that are positive for First Nations, in the end it is an honour-based duty of the Crown, one that is closer to noblesse oblige and falling well short of the ideal of a nation-to-nation relationship.